DETERMINANTS OF ISLAMIC BANKING FINANCIAL PERFORMANCE: THE ROLE OF ASSETS AND INTERMEDIATION IN PALESTINE - Ahmad Aufal Marom; Ahmad Tibrizi Soni Wicaksono (Indonesian Scientific Journal of Islamic Finance, 2026)
The Islamic banking sector in Palestine faces complex challenges due to the prolonged conflict, which has significantly impacted the stability of the domestic economy and financial system. Despite extreme geopolitical pressure, Islamic banks in the region have demonstrated robust operational resilience and stability through robust asset management and optimization of their intermediation function based on Islamic Sharia principles. This study analyzes the influence of total assets, total investment, and total financing on the financial performance (income) of Palestinian Islamic Banks during the 2015–2024 period. Using a quantitative approach with multiple linear regression (OLS) based on 120 monthly observations, this study estimates two test models: a baseline model and a model with control variables (deposits and stock prices). The partial analysis results indicate that total assets and total financing have a positive and significant influence on financial performance in both models, confirming their role as risk absorbers and primary sources of bank income in conflict zones. Meanwhile, total investment has a significant influence in the opposite direction, namely negative in the baseline model due to short-term volatility and becoming positive after the inclusion of control variables. Simultaneously, these three main variables significantly influenced financial performance, with an R-squared value of 32.52% in the baseline model, which then increased to 61.76% in the control model. In conclusion, asset size, investment effectiveness, and financing quality are the main foundational pillars determining the resilience and continuity of Islamic banking operations amidst Palestinian geopolitics.